Study on Effect of Striatal mGluR2/3 in Alleviating Motor Dysfunction in Rat PD Model Treated by Exercise Therapy - Chen, Ping; Li, Xiaodong (Frontiers in Aging Neuroscience, 2019)
This study focuses on the effect of exercise therapy in reducing the concentration of extracellular glutamate (Glu) in striatal neurons in a rat PD model by up-regulating the expression of group II metabotropic glutamate receptor (mGluR2/3), so as to alleviate motor dysfunction in the rat PD model. Adopted neurotoxin 6-Hydroxydopamine (6-OHDA) was injected into the right medial forebrain bundle of the rats to establish the semi-lateral cerebral damage PD model. The apomorphine-induced rotational behavior test combined with immunohistochemical staining of tyrosine hydroxylase (TH) in the substantia nigra and striatum were performed to assess the reliability of the model. The exercise group was intervened with treadmill exercise for 4 weeks (11m/min, 30min/day, 5d/week) one week after the operation. The open field test was performed to assess the locomotor activity of the rats; the Western blot technique was used to detect substantia nigra TH and striatal mGluR2/3 protein expressions; RT-PCR was applied to detect striatal mGluR2 and mGluR3 mRNA expressions; microdialysis-high-performance liquid chromatography method was adopted to detect the concentration of extracellular Glu in striatal neurons. The result verified that exercise intervention may exert an effect in alleviating motor dysfunction in the rat PD model by up-regulating the striatal mGluR2/3 protein expression, reducing the Glu release at the presynaptic terminal, and relieving the excitotoxicity to the postsynaptic membrane.